Evaluation of JAK2V617F Mutation Patients with Non-CML Myeloproliferative Neoplasms by ARMS-PCR - K Alimoghaddam; SA Mousavi; N Einollahi; GR Togheh; B Chardouli; Sh Ferdowsi; A Ghavamzadeh; F Nadali; SH Ghaffari (Tehran University of Medical Sciences, 2008)
Background and Aim : Myeloproliferative neoplasms are clonal and heterogeneous disorders of hematopoietic stem cells lead to increase of one or more cell lines in the blood. Recently, the acquired mutation JAK2 V617F has been described in the majority of patients with myeloproliferative neoplasms (MPNs).This mutation is characterized by a G to T transverse at nucleotide 1849 in exon 12 of the JAK2 gene, located on the chromosome 9p, leading to a substitution of valine to phenylalanine at amino acid position 617 in the JAK2 protein. The aim of this study was to assess the prevalence of JAK2 mutation in MPN patients.Materials and Methods: In this experimental study we evaluated JAK2 mutation in 58 patients with MPNs by simple randomized sampling. The mutation was detected by ARMS-PCR in patients.Results: The JAK2 V617F mutation was detected in 86.6% (26/30) of patients with polycythemia Vera, 46.6% (7/15) of patients with essential thrombocythemia and 61.5% (8/13) of patients with idiopathic myelofibrosis. Polycythemia Vera patients carrying the mutation displayed a higher levels of WBC (p=0.03) and 61.5% (16/26) of these patients were females. The differences in other groups were not significant. The mutation was confirmed by sequencing.Conclusions: Our Results show similarity with other studies. Thus, ARMS-PCR can be applied as differential diagnosis test for detection of JAK2 mutation in suspected patients with MPNs.